PENGARUH KEAHLIAN KOMITE AUDIT, AUDIT TENURE, KOMITE AUDIT WANITA, DAN DEWAN KOMISARIS WANITA TERHADAP KUALITAS LABA (STUDI EMPIRIS PADA PERUSAHAAN LQ-45 PERIODE 2016-2019) - Angelia Febriani Tampubolon; Darmae Nasir; Agus Kubertein (Universitas Palangka Raya, 2022)
The purpose of this research is to determine the effect of audit committee experts, audit tenure, women on audit committees, and women board of comissioners on earnings quality. Study on componies listed in LQ-45 on the IDX 2016-2019. This study uses a type of quatitative research by using purposive sampling as data analysis. This study uses secondary data in the form of docementation, namely company annual report data on the IDX which includes audit committee experts, audit tenure, women on audit committees, women board of comissioners, and earnings quality, 2016-2019. The number of LQ-45 componies sampled in this study were 31 componies with criteria that were consistenly included in the index LQ-45 listed on IDX and having complete data and information for variable measurement. The data has been obtained is then analyzed using the SPSS version 25 application tool. The results of this study indicate that audit comittee experts are positive and significant to earnings quality and audit tenure has a negative and significant to earnings quality. Meanwhile, women audit committee and women board of comissioners have no significant effect on earnings quality. The ablity of the independent variable in explaining the dependent variable is 42,5%, meanwhile the remaining 57,5% is influced by other variables not exmined in this study